Determination of Biomechanical Properties of Rattan Cane in the Design and Fabrication of Prosthetic Foot - Kelechi, Kelechi D.; Ndubuka, Gideon I. N; Onwukamuche, Kingsley C.; Ofoegbu, Michael C.; Elueke, Ugochi C.; Igwe, Alice C.; Okafor, Wilson C.; Okey-mbata , Chioma C.; Ekezie, Jervas (Research Developments in Science and Technology Vol. 1, 2022)
In designing prosthetics for amputees, quality and quantity of materials determine device tensile, flexural, extension and compression strength as well as energy distribution when load is applied. Biomechanical properties contribute in combination to any device longevity and resolution force effect to gait expression. The analysis should reveal the importance of rattan cane as bio-material in medical rehabilitation technology. The local points of availability should encourage Practitioners to adopt methods of use in design and fabrication of low cost prosthetics that the application will gain the acceptance of Amputees for good and quality life expectancy. Four different dry rattan canes were sampled and subjected to biomechanical analysis, and sample 3 had highest tensile strength with ultimate tensile strength of 11.5N/mm2 revealed when load at break of 668.18N applied, and modulus 1033.90MPa with ductility of 7.33 mm were resultant. While average ultimate tensile strength of 8.68N/mm2 was sustained by load at break of 396.66N, modulus of 1119MPa and ductility of 9.5mm was confirmed of rattan cane. Highest flexural strength of 34.43N/mm2 resulted from load at break of 32.82N, modulus 255.65MPa and elongation of 66.81mm was dictated of sample 3, and an average Flexural strength of 26.4 N/mm2 occurred when load at break of 16.04N, modulus 229.16MPa produced elongation (ductility) of 55.1mm on rattan cane. The highest load resistance was shown by sample 3 at compressive strength of 8.79MPa when on load at break of 330N, modulus 622.53MPa resulted. While sample 4 had the highest compressive strength of 9.94MPa when load break at 309N exerted modulus 283.14MPa. Gait analysis revealed terminal swing and heel strike of chosen height 8cm and deformity 0cm while early and mid stance of 0.3cm and 7.7cm were respectively for deformity and height.